2014
DOI: 10.14198/jhse.2014.9.proc1.18
|View full text |Cite
|
Sign up to set email alerts
|

Physical self-efficacy in women’s artistic gymnastic between recreational and competitive level

Abstract: Gomez-Paloma, F., Rio, L. & D'Anna, C. (2014). Physical self-efficacy in women's artistic gymnastic between recreational and competitive level. J. Hum. Sport Exerc, 9(Proc1), pp.S341-S347. In Bandura's theory (1997, 2001), self-efficacy is the cognitive mechanism that mediates information on personal capacities to successfully execute necessary courses of action in a specific domain. It is theorized that self-efficacy belief influences motivation, affect and behaviour. Self-efficacy regarding motor activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Regarding self-efficacy levels, our findings are in line with literature (Gomez-Paloma, Rio, & D'Anna, 2014): the difference between the values of the two levels of gymnasts showed that the élite group is higher in physical self-efficacy in all items than the recreational group. In fact, the artistic gymnastic allows to experience, during training, feedback on personal success performance that are the most effective in increasing self-efficacy for physical activity (Ashord, Edmund, & French, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding self-efficacy levels, our findings are in line with literature (Gomez-Paloma, Rio, & D'Anna, 2014): the difference between the values of the two levels of gymnasts showed that the élite group is higher in physical self-efficacy in all items than the recreational group. In fact, the artistic gymnastic allows to experience, during training, feedback on personal success performance that are the most effective in increasing self-efficacy for physical activity (Ashord, Edmund, & French, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Be resolute, work regularly and constantly, facing the difficulties and obstacles be determined, are basic aspects to the agonistic activity in all sporting activities. The choice of a competitive level is mainly conditioned by the psycho-physical conditions of the athlete and by their personal motivation towards that sport, but it strongly influences performance and competitive results the sense of the perceived efficacy (Gomez Paloma et al 2014).…”
Section: Introductionmentioning
confidence: 99%